Costa Rica's ecological restoration - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Guanacaste National Park Tropical, ecological and cultural restoration / Janzen. D.H 1986 National Parks Foundation and the State Open University Costa Rica 103 pp